International Accounting Standard I4: reporting financial information by segment and its audit implications / Nik Abdullah Sani Nik Mohamed - Nik Mohamed, Nik Abdullah Sani (1986)
International Accounting Standard (IAS) I4, Reporting Financial Information by segment, was originally approved by the Malaysian Association of certified Public Accountant (MACPA) for financial statements with accounting period beginning on or after January 1983; but adoption of the standard was later postponed and a two years moratium was given. Recently MACPA confirmed that the standard is to be mandatory for financial statements with periods beginning on or after January 1985*